Willem Boshoff, artist's monograph and catalogue - (:unkn) unknown (My University, 2013)
Willem Boshoff’s work articulates around a pivotal date, April 1994, the first democratic elections in South Africa. He may choose to work gigantic rocks of granite or establish vast installations of accumulated material. The artist claims that his work is based on language, often taking the form of Dictionaries. While reviewing the main questions by artists of the twentieth century, texts or artworks from Europe are systematically tested against their South African counterpart. Boshoff’s attitude is determined by a melancholic questioning of his role as a creator linked to a political situation and cultural milieu. He discovers more dynamic ways of presenting gestures when his artistic activity is related to the way of life of a druid. As a conscientious objector he learnt that it is often better to hide the true signification of a sign or to disqualify a text. Boshoff’s “Notes towards a blind Aesthetic”, where the essential is not visible, invent a dictionary to be read with the hands. Questioning perception theories provides the artist with a way of capsizing the occidental world towards patterns of thinking that he can claim for himself. The multiplicity of languages in South Africa opens up to questions of memory, ecology, disappearance, mental space as a site of creation, experiments with the limits of the fictional. The druid is one exceptional character amongst others in the contemporary art world. Boshoff obliges his visitor to participate in an act of translation which is given provisional but tangible form in such works as “Writing in the Sand” and the “Gardens of Words”. The druid becomes the guardian of words and plants in danger of being forgotten also safeguarding them against being petrified or fossilized into a set theory or dogma. Kindred spirits working on all continents are: Sarkis, Mofokeng, Baumgarten, Mudzunga, Ulrichs, Kosuth, Wafer, Bochner, Gette, Filliou, Darboven, Alÿs, Acconci, Langa, Marshall McLuhan and
Keywords: African Research